Clinical and Endoscopic Features in Patients with Inflammatory Bowel Disease and Serrated Epithelial Change - Vaitiekunas, Laurence; Ramaswamy, Pradeep Kakkadasam; Pillai, Sooraj; Willis, Timothy; Mohsen, Waled (Journal of Digestive Endoscopy, 2025)
Serrated epithelial change (SEC) is an increasingly recognized histologic finding in patients with inflammatory bowel disease (IBD) and may be associated with an increased risk of colorectal dysplasia. SEC is defined as colonic mucosa with goblet cell–rich epithelium and serrated crypt architecture without basal crypt distortion or dysplasia. This study aimed to characterize the clinical, endoscopic, and histologic features of SEC in IBD patients and determine the incidence of associated dysplasia.A retrospective single-center study was conducted at a tertiary referral hospital. IBD patients with histologically confirmed SEC from colonic biopsies between January 1, 2015 and December 31, 2024 were identified via pathology database searches. Patients without follow-up colonoscopy or flexible sigmoidoscopy were excluded. Clinical, endoscopic, and histologic data were extracted from electronic records. Descriptive statistics were used to summarize demographics, endoscopic findings, and histologic data. Median values were reported for age and follow-up time; mean values described disease duration.Twenty-six IBD patients (16 Crohn's disease, 10 ulcerative colitis) with SEC were analyzed (14 males; median age 58 years). Mean disease duration was 15 years, with a median follow-up of 24.5 months. The estimated prevalence of SEC was . A total of 30 SEC specimens were identified, most commonly located in the cecum (30%), rectum (23.3%), and transverse colon (16.7%). SEC presented as nodular or polypoid lesions in 60% of cases and was detected by high-definition white light endoscopy in 61.5% of patients. Multifocal SEC occurred in 19.2% of patients. Endoscopic and histologic inflammations were present in approximately half of the cases. Only one patient (3.8%) developed low-grade dysplasia adjacent to SEC.SEC was predominantly observed in patients with long-standing IBD as polypoid or nodular lesions proximal to the splenic flexure and associated with mucosal inflammation. A solitary case of colorectal dysplasia was observed. Larger prospective studies are needed to clarify SEC's role in colorectal carcinogenesis and to guide dysplasia surveillance strategies in IBD.
Keywords: serrated epithelial change; inflammatory bowel disease; dysplasia; endoscopy